2022
DOI: 10.1016/j.ctrv.2021.102323
|View full text |Cite
|
Sign up to set email alerts
|

Gene-expression signatures to inform neoadjuvant treatment decision in HR+/HER2− breast cancer: Available evidence and clinical implications

Abstract: Over the last few years, the indication for chemotherapy use in HR+/HER2− early BC has been significantly modified by the introduction of gene-expression profiling. In the adjuvant setting, several gene-expression signatures have been validated to discriminate early stage HR+/HER2− BC with different prognosis and to identify patients for which adjuvant chemotherapy can be spared. Considering their ability to optimize the choice of adjuvant treatment and the increasing use of neoadjuvant approach in early BC, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Beyond this, we could utilize machine learning to derive multi-gene expression signatures that predict drug responses to specific treatments. 63 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond this, we could utilize machine learning to derive multi-gene expression signatures that predict drug responses to specific treatments. 63 …”
Section: Discussionmentioning
confidence: 99%
“…Beyond this, we could utilize machine learning to derive multi-gene expression signatures that predict drug responses to specific treatments. 63 Resistance to therapy could be innate or acquired. 64 Multiple studies have demonstrated the importance of clonal diversity and dynamics in resistance to therapeutic agents, 65 and the use of model systems like PTCs can be extremely useful in supporting clonal expansion studies about the process of acquired resistance.…”
Section: Discussionmentioning
confidence: 99%
“… 73 , 74 Moreover, some trials have added cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) or mammalian target of rapamycin inhibitors to endocrine therapy and investigated whether 21-RS can be used as a biomarker to predict neoadjuvant efficacy. 75 The PLATO study is attempting to provide personalized neoadjuvant therapy to patients with luminal A breast cancer using the 70-gene assay in the hope of improving breast conservation rates. 76 The study is expected to be completed in 2025.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the ASCO guidelines do not recommend the use of gene expression assays to guide clinical decision-making for neoadjuvant therapy. 75 , 77 Therefore, further large sample analyses are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…As a common treatment of cancer, neoadjuvant chemotherapy (NAC) is usually implemented to treat patients with locally advanced BC with the aim of reducing tumor size and allowing more breast conservative therapy to be performed ( 14 ). The therapeutic effect of NAC varies significantly in term of some factors, such as expression of hormone receptors and menopausal status ( 15 , 16 ). A clinical study showed that antibiotic administration leads to a reduction in NAC efficacy and was associated with worse BC prognosis ( 17 ).…”
Section: Introductionmentioning
confidence: 99%